Optimalisasi Implementasi KMA Melalui Perencanaan Berjenjang: Antisipasi Input Heterogen dan Penyetaraan Kompetensi Bahasa Arab - Ammar Zainuddin; Ubay Harun; Endang Munawar (JURNAL ILMIAH GEMA PERENCANA, 2025)
This paper analyzes official documents from the Ministry of Religious Affairs (KMA No. 183/2019, No. 184/2019, and No. 347/2022) and Arabic language textbooks across levels (MI grade 6, MTs grades 7 & 9, and MA grade 10) to examine the application of the Scope–Sequence–Continuity (SSC) principle in Arabic language learning and to design an Arabic language learning plan that is adaptive to input heterogeneity in Madrasahs. This research uses a qualitative method with a content analysis approach to KMA documents and official textbooks from the Ministry of Religious Affairs. The combination of regulatory sources and teaching materials allows mapping of SSC outcomes, material sequences, and repetition patterns across levels while testing the consistency between policies and classroom practices. Therefore, the analysis of each chapter is mapped in the SSC matrix and validated through source triangulation and theory triangulation to reveal the gap between the ideals of the policy and the reality of implementation. Research findings indicate that the curriculum has been designed with a relatively consistent SSC foundation, but has not fully anticipated the heterogeneity of student input. This article highlights the curriculum gap, interprets the data through content analysis, and proposes the concept of input differentiation as a novel contribution to Arabic language learning planning.